Analysis of ROA, Interest Rate, FDR, and NPF Effects on Mudharabah Deposit Profit-Sharing Rates in Islamic Banks 2020–2024 - Nida Meilanda Afanin; Suwandi Suwandi; Catur Wahyudi (International Journal of Economics and Management Research, 2025)
This research analyzes the influence of ROA, Reference Interest Rate, FDR, and NPF on the profit-sharing rate of mudharabah deposits at Islamic Commercial Banks from 2020 to 2024. This is a quantitative study using secondary data from annual financial reports. The research uses 9 samples from a population of 16, selected through purposive sampling method. The analysis methods used include descriptive statistics, classical assumption tests, and multiple linear regression with the help of SPSS 27. The results show that the interest rate and FDR have a significant effect on the profit-sharing rate of mudharabah deposits, while ROA and NPF do not show a significant effect. However, simultaneously, all four variables significantly influence the profit-sharing rate. This study indicates that interest rates and FDR are key factors in improving profit-sharing, and emphasizes the importance of banks adjusting their strategies to macroeconomic conditions and the effectiveness of financing. On the other hand, ROA and NPF have proven to have less influence. This research provides practical implications for the management of Islamic banks and investors that adjustments to interest rates and FDR have a greater impact on increasing profit-sharing compared to only focusing on profitability or financing risk. This study also contributes to the literature on Islamic finance by identifying the key factors that influence the profit-sharing rate of mudharabah deposits in the Islamic banking market in developing countries.